Deciphering the effect of UM171 on human hematopoietic progenitor cell fate through clonal analysis - Patrick Coulombe; Elisa Tomellini; Jalila Chagraoui; Nadine Mayotte; Guy Sauvageau (Nature Communications)
Abstract Ex vivo expansion of hematopoietic stem cells (HSC) requires the maintenance of a stemness state while cells are proliferating. This can be achieved via exposure to UM171 which leads to the degradation of chromatin modifiers and prevents the loss of key epigenetic marks. However, the chromatin landscape varies across populations within the hematopoietic system and the effect of UM171 on self-renewal and differentiation potential of different hematopoietic progenitor cells is less characterized. To address this, we use the CellTag barcoding approach to track the fate of individual stem and progenitor cells during in vitro expansion. We show that, in addition to its HSC self-renewing property, UM171 specifically modulates cell fate of a precursor common to erythroid, megakaryocytic, and mast cells in favor of self-renewal and a mast-bias differentiation trajectory. This differentiation bias can be driven by pro-inflammatory signaling pathways that are activated downstream of UM171 and results in an abundant mast cell population that can be transplanted as part of the graft to populate mice tissues in xenotransplantation studies.